The Sociology of the Professions and the Problem of Journalism Education - Anderson, C.W. (Radical Teacher, 2014)
As part of this special issue on the occupations and the sociology of the professions, this article probes how the complexities of journalism’s professional status play out in pedgagically in the classroom. The author argues that the current turmoil in journalism, and in journalism education, cannot be attributed to technology alone or economics alone but are a part of a deeper, older professional uncertainty amongst journalists. The author concludes wth an argument that the liberal arts should play a greater role in the education of 21st century journalists.